Quantifying Sectarian Bias: A Methodological Analysis of Jarh wa Ta'dil on Abdurrazzaq al-San'ani - Alkadri Alkadri; Hadari Hadari (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2026)
The conflict of Abdurrazzaq's undeniable scientific authority and claims of his theological deviation by hadith critics. As a result, some criticized (jarh) and others praised him (ta'dil). Therefore, research on Abdurrazzaq is needed. The aim is to create a map to identify sectarian bias in jarh wa ta'dil and its causal factors. The research method uses library research with a sanad criticism approach. Data analysis is in the form of content analysis by classifying the percentage of jarh wa ta'dil levels and providing their meaning. The data source is the book Rijal al-Hadith. Results: jarh wa ta'dil quantification map: (1) there are 36.8% who accept and do not report Shia, (2) there are 36.8% who accept but report Shia, (3) there are 10.6% who reject and do not report Shia, (4) there are 10.6% who reject but report Shia, (5) there are 5.2% who reject due to old age. Conclusion: The majority of hadith critics accept Abdurrazaq's narration due to Abdurrazaq's intellectual integrity, the influence of his Sunni teachers, and the distance from the tahkim event. Sectarian bias occurs in the form of Shia claims. Most hadith critics are moderate, accepting Abdurrazaq's narration, and some are radical, rejecting Abdurrazaq due to their skeptical views of Shia. Moderation, open-mindedness, and objectivity in hadith studies have transcended sectarian boundaries. This study has broad methodological implications for refining the concept of 'adl in relation to other sectarian narrators in contemporary hadith discourse.